Reducing red light proportion in full-spectrum LEDs enhances runner plant propagation by promoting the growth and development of mother plants in strawberry - Chen, Jian; Ji, Fang; Gao, Rongwei; He, Dongxian (Frontiers in Plant Science, 2024)
Full-spectrum light-emitting diodes (LEDs) have gradually replaced narrow-spectrum LEDs and are widely used in plant factories with artificial lighting (PFALs). However, the specific effect of LED light quality on dry mass allocation in runner plant propagation remains unclear. Hence, we cultivated “Akihime” strawberries as mother plants for 115 days to conduct runner plant propagation experiment under white LEDs (W100), white and red LEDs (W84R16 and W55R45), red and blue LEDs (RB100), and red, blue and green LEDs (RB80G20) in PFALs, and determined key factors affecting dry mass accumulation and allocation among mother plants and runner plants based on growth component analysis. The results showed that the net photosynthetic rate and total leaf area in mother plants in W100 increased by 11% and 31%, respectively, compared with W55R45. In comparison to W84R16 and W55R45, W100 increased the dry mass (23%–30%) of runner plants mainly by increasing the total dry mass (TDM) (23%) of strawberry plants, without significantly affecting the fraction of dry mass partitioning to runner plants. However, the number of runners in W55R45 was 5.1 per plant, representing only 78% of that in W100. Compared with RB100, RB80G20 significantly increased the number of runner plants and runner numbers by 16% and 19% to 13.0 per plant and 5.8 per plant, respectively. The partial replacement of blue light with green light in RB80G20 induced a shade avoidance response in runner plants, resulting in a 55% increase in the total leaf area of runner plants compared with RB100. Data from growth component analysis showed that compared with red and blue LEDs, white LEDs increased the TDM of runner plants by 83% by increasing the plant TDM accumulation (44%) and the fraction of dry mass partitioning to runner plants (37%). Additionally, the dry mass (g) of runner plants per mol and per kilowatt-hour under in W100 were 0.11 and 0.75, respectively, significantly higher than other treatments. Therefore, reducing red light proportion in full-spectrum LEDs is beneficial for strawberry runner plant propagation in PFALs.